Parenting styles perceived by teenagers and school achievement - Pires, Mónica (2016)
Parenting styles (PS) are parents’ attitudes towards their children’s overall development and education. By establishing the family’s environment and parents’ behaviours, PS have been the focus of developmental psychology and family studies, namely in relation to child outcomes. This cross-sectional smdy analyses the impact of perceived PS by adolescents regarding their school achievement. 110 boys and 118 girls in years 5-9 of schooling (M= I 2.60, 5m 1.82) from a state school in Lisbon answered a demographic form and the Parental Authority Questionnaire for both parents. Their grades and the number of retentions were analysed. Results show that authoritative parenting correlates to higher grades and berter school achievement. Permissive and authoritarian styles correlate to worse school results (grades and number of years held back). Although PS may vary according to cultural contexts, these results are in line with previous international research findings that show that parents’ authoritativeness is associated with better children outcomes arid school achievement. Age and school level have a significant effect on PS. Older and more educated parents are perceived as less permissive and authoritarian. No level of agreement between the PS of mother/father-teenager was found, suggesting that the parents perceive themselves differently than their children. The results contrtbtite to parenting styles' knowledge within the Portuguese cultural context. They are also useful for organizing future, evidence- based interventions regarding parenting programmes and school underachievement and dropout preventing programmes.